Analysis and design of induction motor applying Matlab - Mohd Azfitry, Zolkhifly (Universiti Malaysia Perlis, 2009)
Function of Induction motor is a three phase AC motor and is the most widely used machine. An Induction motor has basically two parts; Stator and Rotor. The Stator is made up of a number of stampings with slots to carry three phase windings. It is wound for a definite number of poles. Two types of rotors are used in Induction motors, Squirrel-cage rotor and Wound rotor. A squirrel-cage rotor consists of thick conducting bars embedded in parallel slots. These bars are short-circuited at both ends by means of short-circuiting rings. A wound rotor has three-phase, double-layer, distributed winding. It is wound for as many poles as the stator. The three phases are wyed internally and the other ends are connected to slip-rings mounted on shaft with brushes resting on them. The function of MATLAB programming is provides an interactive and integrated environment that allows performing mathematical computations, generating plot, writing programs and creating graphical user interface. It has a number of add-on software modules called tool boxed that perform more specialized computations. From this project, it can find the value of calculation and the value of Induction Motor parameter using MATLAB Programming.